2016
DOI: 10.1016/j.elecom.2016.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical deposition of bismuth telluride thick layers onto nickel

Abstract: Bismuth telluride (Bi 2 Te 3 ) is the currently best performing thermoelectric (TE) material in commercial TE devices for refrigeration and waste heat recovery up to 200°C. Up to 800 μm thick, compact, uniform and stoichiometric Bi 2 Te 3 films were synthesized by pulsed electrodeposition from 2M nitric acid baths containing bismuth and tellurium dioxide on 1cm 2 nickel (Ni) substrates at average film growth rates of ~50 μm/hour. Pre-treatment of the Ni substrate was found to significantly enhance the adhesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…These layers become unstable as the layer thickness increases. For this reason, only a small number of studies have been successful in synthesizing thick films of BiTe and SbTe [3,14,15,16,21]. As shown in Figure 8a, although a 200-µm-thick film can be grown using the constant method at a high deposition rate of approximately 30 µm/h, only 20 µm of the thickness is actually of good quality (Figure 8b).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These layers become unstable as the layer thickness increases. For this reason, only a small number of studies have been successful in synthesizing thick films of BiTe and SbTe [3,14,15,16,21]. As shown in Figure 8a, although a 200-µm-thick film can be grown using the constant method at a high deposition rate of approximately 30 µm/h, only 20 µm of the thickness is actually of good quality (Figure 8b).…”
Section: Resultsmentioning
confidence: 99%
“…Many non-aqueous additives have been researched for Bi 2 Te 3 : ethylene glycol [ 6 , 7 ] dimethyl sulfoxide [ 8 , 9 ], ethanol [ 10 ], ionic liquids (choline chloride) [ 11 , 12 ], molten salt (AlCl 3 –NaCl–KCl) [ 13 ], and polyvinyl alcohol [ 14 ]. Additionally, the appearance of the Bi 2 Te 3 soluble anode is proven to enhance a homogeneous composition of deposited films in References [ 14 , 15 , 16 ]. In this work, another possibility of a deposition of thick and stable thermoelectric films has been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulse periodic potential control was used in this work to maintain uniform mass transport conditions over the whole deposition period and to control metallic bismuth oxidation, while preventing bilayers (Bi 2 ) anodic oxidation. Additionally, pulse deposition favors high substrate-film adhesion and proper film solidity [11][12][13][14][15][16]. Bi-Te binary phase diagram [17] (Figure 1) predicts the formation of a series of stoichiometric compounds.…”
Section: Introductionmentioning
confidence: 99%
“…However, the halfquantitative results did give the information of the change in compositions caused by both the organic-inorganic complex formation and the heat treatment. In view of the accuracy of EDS and XRD on quantitative elemental analysis, earlier studies showed that the difference in the results between the two techniques is less than 2% based on the Bi-Te atomic ratio measurements for the bulk alloys, particles, and/or thin films [39][40][41][42][43][44][45][46][47][48][49].…”
Section: Energy Conversion Propertymentioning
confidence: 99%